استراتيجيات تعليم اللغة العربية باستخدام نظرية الذكاءات المتعددة لمنيب شاطب: Arabic - Ritonga, Ade; Rahmat Raja; Ahmad Zaky (Universitas Djuanda, 2025)
This article aims to describe the application of the educational concept based on the